The Effect of Anticoagulants on Early Implant Failure: A Retrospective Cohort Study - Liat Chaushu; Noa Perez; Daniele Botticelli; Samuel Porfirio Xavier; Roni Kolerman; Daya Masri (Journal of Functional Biomaterials, 2023)
Background: Anticoagulants (AC) are among the most often prescribed drugs in the world. Data regarding ACs’ effect on the osseointegration of dental implants is lacking. Purpose: The aim of the present retrospective cohort study was to evaluate the effect of anticoagulants (AC) on early implant failure (EIF). The null hypothesis was that the use of AC increases the incidence of EIF. Materials and Methods: The research included 687 patients who underwent 2971 dental implant placements in the department of oral and maxillofacial surgery in Rabin medical center, Beilinson hospital, by specialists in oral and maxillofacial surgery. The study group comprised 173 (25.2%) patients and 708 (23.8%) implants using AC. The rest of the cohort served as a control. A structured form was used to collect data at patient and implant level. EIF was defined as implant failure within a period of up to 12 months from loading. EIF was the primary outcome parameter. A logistic regression model was used to predict EIF. Results: Implants placed in individuals ≥ 80 (odds ratio (OR) = 0.34, p = 0.05), and ASA 2/3 vs. ASA 1 individuals (OR = 0.30, p = 0.02/OR = 0.33, p = 0.03, respectively) had decreased odds of EIF, and implants in those using anticoagulants (OR = 2.64, p = 0.01) had increased odds of EIF. At the patient level, the odds of EIF in ASA 3 (OR = 0.53, p = 0.02) and IHD (OR = 0.40, p = 0.02) individuals decreased. In AF/VF (OR = 2.95, p = 0.01) individuals, EIF odds increased. Conclusions: Within the limitations of the present study, the use of AC is significantly associated with an increased likelihood of EIF: the OR was 2.64. Future research is required to validate and examine the prospective impact of AC on the osseointegration phenomena.